A geometallurgical study of the quartz dominant ore varieties in a polymetallic base metal sulphide deposit, Northern Cape, South Africa - Stroebel, Graeme B. (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.